Trajetórias das quitandeiras negras na cidade do Rio de Janeiro: a rua como espaço de circulação, agenciamento e territorialidade (1860-1902) - Cristina Antunes Divano Cunha; Patrício Pereira Alves de Sousa (Nuevo mundo - Mundos Nuevos)
The article analyzes the territorialities of Black women street vendors (quitandeiras) in the city of Rio de Janeiro at the end of the 19th century through the circulation of their geo-alimentary knowledge. The reflection explores the diasporic movements and knowledge productions of these women in public spaces controlled by hegemonic power. In the transatlantic slave trade, the system of quitandas, common among African women, was redefined in Brazil, transporting epistemologies and cosmologies through culinary practices. Facing suspicion while occupying public spaces, Black quitandeiras became agents of their own, resisting violence and denial of belonging. The research in the Digital Newspaper Library analyzed the activities of Black quitandeiras in Rio de Janeiro between 1860 and 1902. This period spanned from the beginning of the tensions within the slavery system to the urban reforms that reshaped the central territories occupied by the Black and poor population. The research concluded that food knowledge was revealed as strategies of resistance, resignification and preservation of memory during compulsory displacements, with the greengrocers constituting themselves as active agents in the construction of identities, territorialities and resistances, using their knowledge as a form of power and survival in an adverse context. food knowledge emerged as strategies of resistance, reinterpretation, and preservation of memory during forced displacements, with the quitandeiras becoming active agents in the construction of identities and resistances, using their knowledge as a form of power and survival in an adverse context.